2017
DOI: 10.1007/s11136-017-1496-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise, vegetable and fruit intake and health-related quality of life in Chinese breast cancer survivors: a cross-sectional study

Abstract: Physical exercise, enough vegetable and fruit intake are positively associated with HRQOL of BCS. BCS who adopted several healthy behaviors simultaneously had better HRQOL than one healthy behavior alone. Healthy behaviors, including engagement in exercise, proper diet, especially comprehensive lifestyle behavior interventions, should be valued in improving HRQOL of BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…The present study indicated that people with low levels of consumption of vegetables and fruits were more likely to develop prediabetes 26 . Additionally, the consumption of abundant vegetables and fruits could improve the survival of individuals with cancer 27 . Dairy, fish and eggs are good sources of high-quality protein, minerals, vitamins and fats.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicated that people with low levels of consumption of vegetables and fruits were more likely to develop prediabetes 26 . Additionally, the consumption of abundant vegetables and fruits could improve the survival of individuals with cancer 27 . Dairy, fish and eggs are good sources of high-quality protein, minerals, vitamins and fats.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond dietary habits, the ACS guidelines for cancer survivors also recommend to achieve and maintain a healthy weight and to engage in regular physical activity. Accordingly, several lines of evidence from observational studies underlined the role of weight management and exercise to improve health status and QoL of breast cancer survivors [24][25][26][27][28]. Moreover, it has been demonstrated that a multidisciplinary rehabilitation program, based on occupational and physical counseling, supported a return to work by reducing fatigue and increasing working ability and QoL [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies examining the HRQoL of women with breast cancer have been conducted in women at least four months after a breast cancer diagnosis (9,10,12). By this time, women have begun their initial treatment process, and have had some time to adjust to their condition.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many researchers are committed to exploring the in uencing factors affecting the HRQoL of breast cancer patients, and hope to improve the overall health of breast cancer patients by changing these factors. Psychosocial factors, sociodemographic variables, and medical variables have been identi ed as predictors of HRQoL in cancer patients (7,9), but current research on the impact of various lifestyle habits factors on the HRQoL of breast cancer patients is still controversial (12,13). Mosher and Danoff-Burg reviewed studies on age differences in psychological adjustment to breast cancer and suggested age may be best viewed as a risk factor for distress with other variables operating to produce this demographic difference (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation